On the Lebesgue Inequality on Classes of $\bar{ψ}$ -Differentiable Functions - Zaderei, N. N.; Zaderei, P. V. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We consider the deviations of Fourier sums in the spaces ${C^{\bar{ψ}}}$. The estimates of these deviations are expressed via the best approximations of the $\bar{ψ}$ -derivatives of functions in the Stepanets sense. The sequences $\bar{ψ} = (ψ_1, ψ_2)$ are quasiconvex.